Analytické hodnotenie mono[{3-[4-(2- -etoxyetoxy)-benzoyloxy]-2- -hydroxypropyl}-izo- propylamónium]fumarátu - Malík, Ivan; Andriamainty, Fils; Sedlárová, Eva; Cizmárik, Jozef; Galisinová, Jana; Mokrý, Petr; Csöllei, Jozef; Karlovská, Janka; Lukác, Milos (Ceska a Slovenska farmacie, 2011)
The present paper deals with a complex spectral and physicochemical evaluation of mono[{3-[4-(2-etoxyetoxy)-benzoyloxy]-2-hydroxypropyl}-isopropylammonium]fumarate, a potential ultrashort acting beta1-blocker. The identity of the substance under study (labelled as UPB-1) was confirmed by 1H- and 13C-NMR spectra as well as IR spectrometry. The determined fundamental physicochemical characteristics included the determination of the melting point, solubility in a spectrum of solvents, verification of purity (adsorption thin-layer chromatography), determination of surface activity (Traube's stalagmometric method), acidobasic characteristics (pK(a) value by means of alkalimetric titration), determination of log epsilon values using spectrophotometry in UV/VIS region, as well as the evaluation of the effect of acid and basic media on the stability of the substance under the study. Other experimentally determined parameters were lipohydrophilic characteristics essayed by means of RP-HPLC (log k'), and the shake-flask method was employed to determine the values of the partition coefficients P(exp) (resp. log P(exp)) in different lipohydrophilic media. On the basis of log P(exp-) data, the ability of the substance to penetrate the hematoencephalic barrier was predicted. To determine the UPB-1 content, RP-HPLC (reversed-phase HPLC) method of the internal standard and UV/VIS spectrophotometry at the wavelength of 260 nm (aqueous medium) and 258 nm (methanol medium) were used.
Keywords: Chemistry, Pharmaceutical; spektrální analýza; Magnetic Resonance Spectroscopy; Adrenergic beta-1 Receptor Antagonists; magnetická rezonanční spektroskopie; fyzikální chemie; Spectrum Analysis; spektrofotometrie infračervená; Chemistry, Physical; Spectrophotometry, Infrared; antagonisté beta-1-adrenergních receptorů; farmaceutická chemie